Implementasi Metode Simple Additive Weighting (SAW) untuk Sistem Pendukung Keputusan Pemilihan Dosen Favorit Mahasiswa - Desyanti, Desyanti; Mesran, Mesran; Windia Ambarsari, Erlin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
College X in Dumai City always strives to continuously improve internal quality so that it can compete with other universities. One effort to improve quality is by assessing lecturer performance every year. So far, the process of selecting outstanding lecturers or favorite lecturers is still based on the subjectivity of those who choose, so there is a lack of transparency in the selection process. This research discusses the application of the Simple Additive Weighting (SAW) method in a decision support system for selecting favorite lecturers at College X, Dumai. Lecturer performance assessment is based on criteria such as discipline, achievement, behavior, responsibility and communication, involving students as respondents. Data was collected through literature studies, interviews, observations and Likert scale-based questionnaires. The calculation process using the SAW method includes normalization of the decision matrix and ranking based on criteria weights. The research results show that the SAW method provides objective, transparent and systematic results in selecting favorite lecturers. The system developed is able to support universities in improving the quality of lecturers through more structured feedback.